Postoperative Urinary Tract Calculi Culture – Is it necessary in Negative Urine Culture Patients? (Nusantara Science and Technology Proceedings, 2022)
Postoperative infection in urinary tract calculi (UTC) cases still become an issue. It is accounted for up to one-tenth of patients experiencing urinary tract infections. Standardized preoperative urine culture help identify bacteria and antibiotic needed for UTC patients. Nevertheless, postoperative infection occurs even though no bacteria were found in urine preoperatively. This descriptive study aims to identify bacteria in calculi. Calculi culture and antibiotic sensitivity tests were carried out in patients with negative urine cultures who underwent endourology procedures from February to June 2022. Thirty-five negative urine culture cases consisting of 23 (46%) males and 12 (24%) females were identified. Positive calculi culture was identified in 11 (31.4%) cases with a previously negative urine culture. Escherichia coli, and Klebsiella pneumoniae were two prominent bacteria found. Among those patients, 5 (45.5%) cases develop SIRS and required antibiotic changes. Our data suggested added benefit of calculi culture in patients with stone disease, especially one enduring endourology procedure. An extensive study with larger sample size is required to decide whether routine calculi culture examination is necessary.